IDENTITAS VISUAL DALAM DESTINATION BRANDING KAWASAN NGARSOPURO - Panindias, Asmoro Nurhadi (Institut Seni Indoensia Surakarta, 2014)
Surakarta city, then known as Solo, has a long history as part of the cultural centers of Java. â€œSoloPast is the Solo Futureâ€, a slogan created by Solo City Government in an effort to make Solo as anicon of cultural heritage preservation. Solo is known as one tourist destination in Indonesia, which isrich in a variety of tourist attractions, ranging from cultural tourism, nature tourism, and culinarytours. Economic development and business in Solo can go hand in hand with the development, preservationof cultural heritage and tourism. Ngarsopuro is an area in front of the Mangkunegaran,which formerly lined electronics stores and antique markets called Triwindu. Ngarsopuro region isseen as a cultural activity. As a tourist destination, Ngarsopuro Region needs to have an identity as adifferentiating factor and promotion. It is necessary for a studies associated with Visual IdentityNgarsopuro area for promoting tourism potential.This design study will design a visual identity for the region as a destination brand Ngarsopuro, soresearch conducts with qualitative studies. To design a visual identity Ngarsopuro Region Solo willrequire methods to acquire the concept and design results, among others, to study and data collectingprimary data and secondary data conducted by interview, observation and documentation of data onthe scope of Ngarsopuro area, potential and excellence and values contained in Javanese culture.The visual identity of a company is not only formed by a logo, but also the supporting visual elementsthat appear in each component company. With consistency in the use of visual elements in a companywill further strengthen the position and identity of the company in the eyes of the visitor or relatedparties. Visual identity also includes some of the constituent elements including the name, logo, colors,and slogan.Keywords: Destination brand, Visual identity, Ngarsopu